Mobility of Zinc in Sandy Soil of Loukkos Area (northwestern Morocco) - Drissi Saad; Abdelhadi Aït Houssa; Ahmed Bamouh; Ahmed Bouaziz; Mohamed Benbella (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2016)
This study investigated the effect of different leaching rates on the downward movement of zinc applied, as fertilizer, on the surface of a sandy soil. The experiment was conducted in polyethylene bags filled to 30 cm depth with sandy soil. A zinc supply of 15.3 10-3 cmolc kg-1 was applied to the soil surface as a solution of zinc sulfate. Three leaching rates were tested: 31 mm, 208 mm and 497 mm. Results showed the absence of zinc in the leachate for all leaching rates. Within the soil profile, the highest content on exchangeable zinc (15.3 10-3 cmolc kg-1) was recorded in the top soil layer (0-10cm) for all leaching rates. In the middle (10-20 cm) and in the lower (20-30 cm) layers, the exchangeable zinc content remained similar to that recorded before leaching (0.76 10-3 cmolc kg-1). The percentage of the cation exchange capacity occupied by zinc in the top soil layer increased after leaching. It averaged 0.35% for all leaching rates while it remained similar to that recorded before leaching (0.03%) for the middle and the lower layers. This increase was linked to the adsorption saturations sites particularly released by manganese, potassium, calcium and ammonium after their downward movement.